Development and evaluation of imiquimod-loaded nanoemulsion-based gel for the treatment of skin cancer - Shital T. Jadhav; Vijay R. Salunkhe; Somnath D. Bhinge; Sandip M. Honmane; Aasha S. Jadhav (SpringerOpen, 2024)
Abstract Background The human skin, as the body's largest organ, is particularly sensitive to many chemical mutagens and carcinogens encountered in daily life. Skin cancer has become a notable global health concern, partly due to increased exposure to environmental pollutants and UV rays. Various treatments are available to treat skin cancer. Imiquimod is approved for the treatment of actinic keratosis and basal cell carcinoma. The present investigation aimed to develop nanoemulsion-based gel with imiquimod (2.5% w/w) and carbopol ultrez 10 NF using a modified method to enhance the solubility, permeation, and therapeutic effectiveness of imiquimod to treat skin cancer. Combinations of rose oil and oleic acid, with Tween 20/Propylene glycol as Smix, were used in the formulation. The formulation underwent evaluation for parameters such as % drug content, in vitro drug diffusion studies, viscosity, skin irritation, in vitro cytotoxicity assay (MTT assay) and the DMBA/ croton oil skin cancer in vivo model. Results The formulation showed a minimum globule size of 118 nm, a zeta potential- 56.26 mV, a PDI of 0.378 and a drug content of 99.77%. In vitro drug release exhibited 45.00% of imiquimod release within 8 h, while approximately 34.32% release was found from the commercial cream. The imiquimod-loaded nanoemulsion-based gel showed significant cytotoxicity (p < 0.001) against the A431 cell line compared to Imiquad cream. The IC50 value of the imiquimod-loaded nanoemulsion-based gel was noted to be 10.76 ± 2.54 µg/mL. In vivo results showed a significant reduction in tumor incidence (16.66%), tumor volume (140.26 ± 3.48 mm3), tumor burden (5.50 mm3) and tumor mass (0.66 ± 0.05 g) compared with the DMBA/croton oil carcinogen treatment control group. Histopathological finding showed the absence of keratinized pearls, epidermal hyperplasia, and acanthosis in the formulation treated group. Conclusion The results revealed that the nanoemulsion-based gel, with half the IMQ concentration of the commercial cream and incorporating Carbopol Ultrez 10NF, is a promising method for treating skin carcinogenesis. It potentially reduces dose-dependent side effects and demonstrating enhanced efficacy. Graphical abstract